Recent advances in drug delivery systems for glaucoma treatment. (June 2022) - Patel, K.D.; Barrios Silva, L.; Park, Y.; Shakouri, T.; Keskin-Erdogan, Z.; Sawadkar, P.; Cho, K.J.; Knowles, J.C.; Chau, D.Y.S.; Kim, H.-W.
Abstract: Glaucoma is a chronic eye disease and the second most leading cause of irreversible impaired vision in the world, which is primarily linked with high intraocular pressure (IOP). The treatment of glaucoma is currently challenging because of the innate mechanics of ocular barriers that limit the penetration of ophthalmic drugs. To tackle this, various carriers (inorganic-, polymeric-, hydrogel-, or contact lens–based) with specialized physical and chemical properties have been intensively studied. These carrier-drug formulations have shown significant improvement in various aspects, such as ocular barriers penetration, bioavailability, sustained release of drug, tissue targeting, and lowering the IOP. The delivery systems can be administered through various routes (intravitreal or periocular injection or systemic route), enabling the drugs to reach the damaged sites and help to recover the damaged optical nerves, thus considered an effective treatment strategy for glaucoma. In this review, we thoroughly investigate the recent advances in ocular delivery formulations focusing on glaucoma, including nanocarrier types, delivery route, and the efficacy in vitro and in vivo, clinical availability, and future outlook. Graphical abstract: Image 1 Highlights: Requirements of nanocarriers for ocular drug delivery Drug formulations in diverse nanocarriers Diverse nanoplatform for drug delivery in glaucoma treatment Promising directions for hydrogel and contact lens-based treatment of glaucoma Applications and clinical challenges in glaucoma treatment